The Role of Employee Engagement and Flexible HRM in Improving Employee Performance - Afiza Afiza; Adi Neka Fatyandri; Evi Silvana Muchsinati (Universitas KH. Abdul Chalim Mojokerto, 2026)
Employee performance is a critical factor for maintaining organizational competitiveness, particularly in specialized service industries such as maritime safety equipment inspection. Employee engagement and flexible human resource management (FHRM) are often considered key drivers of improved job performance. While previous studies have examined the relationship between employee engagement and flexible HR practices, most have focused on sectors such as information technology. Limited research has explored these relationships in the maritime safety service sector, particularly in Indonesia. The study employed a quantitative research method using non-probability sampling with accidental sampling approach. Data were collected from 170 employees across five ship safety equipment inspection companies in Batam (PT Global Marine Safety, PT Sucofindo, PT Devin Marine Safety, PT Mulia Safety Service, and PT Cahaya Samudra Marine). The research utilized PLS-SEM analysis with SmartPLS application, measuring variables through a 10-point Likert scale questionnaire distributed online from November 2024 to January 2025. The results demonstrate that all variables (employee engagement, flexible human resource management, and job performance) exhibit high validity and reliability. Direct path analysis reveals that employee engagement significantly influences both FHRM (β = 0.595, p < 0.001) and job performance (β = 0.545, p < 0.001). However, FHRM does not significantly affect job performance directly (β = 0.211, p = 0.093) and fails to function effectively as a mediator between employee engagement and job performance (β = 0.126, p = 0.069). This study extends the literature by examining employee engagement and FHRM in the maritime safety sector in Indonesia. The findings suggest that employee engagement plays a more direct and dominant role in enhancing job performance than flexible HR practices. Organizations in specialized service industries should therefore prioritize strategies that strengthen employee engagement to improve performance outcomes.